2020
DOI: 10.20944/preprints202004.0219.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Socio-economic Implications of the COVID-19 Pandemic on Smallholder Livelihoods in Zimbabwe

Abstract: The article revisits previous viruses such as Ebola to extrapolate the socio-economic implications of the COVID-19. Using secondary sources and the Sustainable Livelihoods Framework (SLF) to guide understanding, the article argues that unless measures are put in place to safeguard smallholder activities in Zimbabwe, COVID-19 has the potential to reproduce the same catastrophic implications created by Ebola in West African countries where peasant food systems where shattered and livelihoods strategies maimed. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 6 publications
2
32
0
2
Order By: Relevance
“…As outlined in the Introduction, COVID-19 was first identified in the Hubei Province, City of Wuhan, China in the latter part of 2019 [1,17]. Soon after, this disease began to wreak havoc and the devastating effect of the pandemic forced the World Health Organization (WHO) to declare it as a global pandemic [17]. In South Africa, the first confirmed case of COVID-19 was recorded on 5 March 2020.…”
Section: Covid-19 In South Africamentioning
confidence: 99%
“…As outlined in the Introduction, COVID-19 was first identified in the Hubei Province, City of Wuhan, China in the latter part of 2019 [1,17]. Soon after, this disease began to wreak havoc and the devastating effect of the pandemic forced the World Health Organization (WHO) to declare it as a global pandemic [17]. In South Africa, the first confirmed case of COVID-19 was recorded on 5 March 2020.…”
Section: Covid-19 In South Africamentioning
confidence: 99%
“…The outbreak of the COVID-19 as a global pandemic exacerbated the situation in Zimbabwe like in many countries around the globe. Response mechanisms adopted by the Zimbabwean government in tandem with the guidelines provided by the World Health Organization (WHO) resulted in the pronouncement of the nationwide lockdown on the 26th of March 2020 to curb the transmission of the virus (Mhlanga and Ndhlovu 2020). The lockdown measures prescribed citizens to be confined to their homes only to leave to procure basic commodities including medications or as essential workers.…”
Section: Outbreak Of Health Emergenciesmentioning
confidence: 99%
“…COVID-19 affects public health and questions have been raised on its effects on both local and global food structures and their capability to assure reasonable and safe food accessibility and use and sufficient incomes for individuals residing especially in smallholder areas of developing countries. Zimbabwe is one such country in which its household-level food mechanism is upheld through initiatives of the subsistence of smallholder (Mazwi & Mudimu, 2020), cited in (Mhlanga & Ndhlovu, 2020). Zimbabwean smallholders may not only have production and income disturbed, but rather may have problems in having access to food for consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Zimbabwean smallholders may not only have production and income disturbed, but rather may have problems in having access to food for consumption. The World Food Programme indicated that nations with huge level of food insecurity, i.e., a high degree of poverty, are much exposed and less ready for an outbreak pandemic such as the COVID-19 (Mhlanga & Ndhlovu, 2020). Furthermore, COVID-19 had arrived when the Zimbabwean health system was already battling out and when its capacity to contain COVID-19 was slim (Mhlanga & Ndhlovu, 2020), with shortages of health equipment, testing kits, medical stuff equipment and so forth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation